2002
DOI: 10.1093/ndt/17.1.57
|View full text |Cite
|
Sign up to set email alerts
|

C5b–9 and adhesion molecules in human idiopathic membranous nephropathy

Abstract: In IMN, C5b-9 formation may be secondary to IgG and C3 deposition. Proteinuria may contribute to the TIN damage by altering the expression of alpha3beta1 integrins in tubular cells. De novo ICAM-1 and C5b-9 expression within the TIN as well as the activated interstitial cells may be important factors leading to renal damage and renal function impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
1
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 19 publications
1
21
1
1
Order By: Relevance
“…The pathologic changes from renal tissues of Thy-1 N are dependent on complement activation and independent on neutrophil influx (Yamamoto and Wilson, 1987;Brandt et al, 1996). Because recent studies have confirmed that the role of C5b-9 to resident glomerular cells belongs to non-lytic (sublytic) in the majority (Couser et al, 2001;Papagianni et al, 2002;Nauta et al, 2002), deeply exploring the effects of sublytic C5b-9 in Thy-1 N has become a subject of intense inquiry (Pippin et al, 2003;Shimizu et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The pathologic changes from renal tissues of Thy-1 N are dependent on complement activation and independent on neutrophil influx (Yamamoto and Wilson, 1987;Brandt et al, 1996). Because recent studies have confirmed that the role of C5b-9 to resident glomerular cells belongs to non-lytic (sublytic) in the majority (Couser et al, 2001;Papagianni et al, 2002;Nauta et al, 2002), deeply exploring the effects of sublytic C5b-9 in Thy-1 N has become a subject of intense inquiry (Pippin et al, 2003;Shimizu et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Such acquired CR1 deficiency could increase the susceptibility of podocytes to complement activation by antibodies in subepithelial immune deposits (82). As in experimental MN, C5b-9 is assembled on the podocytes of patients with MN, which is evident histologically (26,99) and by examining urine for C5b-9 (65,125). Complicating the utility of urinary C5b-9 measurement is alternative complement pathway activation on proximal tubular cells noted previously, which also can result in the appearance of C5b-9 in the urine of proteinuric patients, including those with MN (85,96).…”
Section: Implications For Human Mnmentioning
confidence: 98%
“…Still, there is a good deal of circumstantial evidence that complement is activated in subepithelial immune deposits, including the presence of C3 and C5b-9 in many cases (48,99) and C3d in all cases of human MN (28); C3d is the stable C3 product generated from iC3b by factor I, presumably relying on podocyte CR1 as a cofactor. Despite these apparent contradictions, it does seem likely that in human MN complement activation is initiated through the classical pathway with possible amplification by the alternative pathway, a scenario that may be more common than previously appreciated (51).…”
Section: Implications For Human Mnmentioning
confidence: 99%
“…Sublethal complement activation occurs on affected podocytes, causing damage and intracellular signaling activation (162,35). It has been well documented that deposition of the terminal components of complement (c5b-9) occurs not only in PHN (3,33,82,135,147) but also in MN in humans (30,49,91,131,133). Moreover, c5b-9 is required in some models of PHN (9,34,124,135).…”
Section: Rat Model Of Passive Heymann Nephritismentioning
confidence: 99%